If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 40 = x + -2 Reorder the terms: 40 + 4x = x + -2 Reorder the terms: 40 + 4x = -2 + x Solving 40 + 4x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 40 + 4x + -1x = -2 + x + -1x Combine like terms: 4x + -1x = 3x 40 + 3x = -2 + x + -1x Combine like terms: x + -1x = 0 40 + 3x = -2 + 0 40 + 3x = -2 Add '-40' to each side of the equation. 40 + -40 + 3x = -2 + -40 Combine like terms: 40 + -40 = 0 0 + 3x = -2 + -40 3x = -2 + -40 Combine like terms: -2 + -40 = -42 3x = -42 Divide each side by '3'. x = -14 Simplifying x = -14
| 40x-4=x+2 | | 4w+10=7w-2 | | 8(k-1)+9(k+3)-2(k-5)=0 | | 150c+1000=2200 | | 150c+1000=1300 | | 8-(y+9)=-2y+12 | | 150c+100=2200 | | 14(m-3)=11m-9 | | x^2-7x+9=-x^2-11x+15 | | (6u^3-4u^2-3u+2)/(3u^2+u-2) | | 2-3x=11+6x | | 3x+9=x-17 | | -3+10=14x-2-13x | | -4(x+3)+4y=17 | | 2t-2=3(t+7) | | 42+5y-3=17y-9-4y | | 42+5y-3=17y-9-4t | | 2x+8=2(x+3) | | 8-7x=16+2x | | 9(x+3)=6(x-1) | | 3t-9=4(t+3) | | 44+4y-16=15y-14-4y | | -3+13=12x-4-11x | | 5(x+2)=(x-7)+53 | | (16+2x)(12+2x)=396 | | 0=x^2/10+9x/10+11/5 | | 4x^2+44x-204=0 | | P(8)=25x^2-24x+615 | | y=-5x/6+50/3 | | 33/2= | | y=-40x+260 | | -.01g+60=0 |